Mastering JBoss Drools 6 : discover the power of Drools 6 and Business Rules for developing complex scenarios in your applications /: discover the power of Drools 6 and Business Rules for developing complex scenarios in your applications. (2016) - Aliverti, Esteban
No abstract available